Essentials of maxillary sinus augmentation - Louise, Francis; Dragan, Oana (Berlin : Quintessence Publishing, 2018)
Sinus augmentation has become a routine surgical procedure to increase the height of the edentulous atrophied posterior maxilla. Numerous techniques have been used successfully, allowing a high survival rate of implants placed after sinus elevation. This book highlights the anatomical landmarks and describes, using clinical cases, the latest ultrasonic devices used for both lateral and crestal approaches, including their possible complications. With step-by-step clinical images, this book will help the clinician to make rational decisions for maxillary sinus augmentation, and to treat any complications that occur during surgery. This is an extremely accessible and up-to-date resource that every dentist should have in their office, for clinical guidance in their treatment planning or when performing sinus augmentation.--
Includes bibliographical references (pages 110-114) and index.
Keywords: Sinus Floor Augmentation -- methods; Sinus Floor Augmentation -- instrumentation; Sinus Floor Augmentation -- adverse effects; Maxillary Sinus -- diagnostic imaging; Dental Implantation; Atlases